Bahasa Inggris - Urmatul Waznah; Khusna Santika Rahmasari; Wulan Agustin Ningrum; Hilda Fitria Wulandari (LPPM Universitas Abdurrab, 2024)
Diabetes mellitus is a disease characterized by increased blood sugar levels (hyperglycemia). One of the enzymes that plays an important role in breaking down oligosaccharides and disaccharides into monosaccharides so that they are ready for absorption is the α-amylase enzyme which can delay and lengthen the digestion time of carbohydrates. Moringa (Moringa oleifera L) is a plant that originates from India and has now spread widely to tropical and subtropical areas throughout the world. Moringa leaves are known to contain the flavonoid, β-sitosterol, which can reduce sugar levels. The aim of this research was to examine inhibitory activity of α-amylase on methanol, n-hexane fraction and ethanol extract of Moringa leaves. The method for data analysis was carried out by obtaining antidiabetic test data, namely the % inhibition value of the α-amylase enzyme activity. From the results of the research that has been carried out, it can be concluded that there is α-Amylase enzyme inhibitory activity with moderate strength in samples of methanol partition and n-hexane partition of Moringa leaves carried out in vitro, with IC50 values of 105.302µg/ ml and 158.29µg/ml. Meanwhile, theMoringa leaves ethanol extract sample was carried out in vitro, with an IC50 value of 81,74 µg/ml.